THE ROLE OF MUTATIONS AND PROMOTIONS ON PERFORMANCE GOVERNMENT EMPLOYEES CIVILIANS IN THE ENVIRONMENT OF UIN IMAM BONJOL PADANG - Herlinda, Alnungki ; Apriyeni, Deltri; Neldawati, Neldawati; Helia, Suhelmi (AIBPM Publisher, 2024)
This research aims to determine the process of implementing transfers and promotions and their role in improving performance. Obstacles are faced and efforts are made to overcome obstacles that arise within the UIN Imam Bonjol Padang environment. The research design is descriptive qualitative. The data used is primary data and secondary data. Primary data was obtained from research sources, consisting of employees who carried out job transfers and promotions. Secondary data is data related to research problems obtained from related agencies through activity reports, documentation studies, etc. Presentation of data in the form of tables, pictures, graphs, and results of direct interviews with research sources. Data analysis was carried out using qualitative methods. The research results show that the transfer and promotion processes carried out are by following the institutional SOP. Transfers are carried out based on suitability between ASN employee competencies and position requirements, position classification, and career patterns, taking into account the principle of prohibiting conflicts of interest. Meanwhile, one of the job promotion processes begins with a Competency Assessment, aimed at mapping civil servants based on position competencies to create superior human resources. The transfer and promotion process plays a role in improving performance by achieving institutional work targets. There are still obstacles in the transfer and promotion process within UIN Imam Bonjol Padang. Based on the results of the study, it is recommended that organizations continue to improve employee capabilities through skills training provided periodically. For this reason, it is necessary to allocate funds from institutions to develop quality human resources for the future progress of UIN Imam Bonjol. Keywords: transfer, promotion, performance, ASN.